Experimental Study on Laser Lap Welding of Aluminum–Steel with Pre-Fabricated Copper–Nickel Binary Coating - Hua Zhang; Huiyan Gu; Dong Ma (Crystals)
In order to solve the problem of poor weld quality caused by brittle metal compounds in the welding of dissimilar metals between aluminum and steel, a pre-welding treatment method of prefabricated copper–nickel binary coating between aluminum and steel has been proposed. Laser lap welding tests and weld performance tests were conducted using 6061 aluminum alloy and DP590 duplex steel with a thickness of 0.5 mm as base materials, with steel on top and aluminum on bottom. The research results indicate that the prefabricated copper–nickel binary coating can effectively suppress the formation of brittle phase compounds of Fe and Al; the increase of copper and nickel elements is beneficial for the formation of tough compounds such as (Fe, Cu, Ni)3Al, (Fe, Cu, Ni)Al3, and CuAl5 in the weld zone; when the thickness of the copper coating is 155 μm and the thickness of the nickel coating is 110 μm, the mechanical properties of the aluminum steel lap welding seam are the best, and the maximum shear force that can be withstood is 208.09 N, which is 56% higher than uncoated sample.